The detection of Coccidioides from ambient air in Phoenix, Arizona: Evidence of uneven distribution and seasonality. (10th September 2019) - Gade, Lalitha; McCotter, Orion Z; Bowers, Jolene R; Waddell, Victor; Brady, Shane; Carvajal, Joseph A; Sunenshine, Rebecca; Komatsu, Kenneth K; Engelthaler, David M; Chiller, Tom; Litvintseva, Anastasia P
Abstract: Coccidioidomycosis is a debilitating fungal disease caused by inhalation of arthroconidia. We developed a novel approach for detection of airborne Coccidioides and used it to investigate the distribution of arthroconidia across the Phoenix, Arizona, metropolitan area. Air filters were collected daily from 21 stationary air-sampling units across the area: the first set collected before, during and after a large dust storm on August 25, 2015, and the second over the 45-day period September 25–November 8, 2016. Analysis of DNA extracted from the filters demonstrated that the day of the dust storm was not associated with increase of Coccidioides in air samples, although evidence of the low-level polymerase chain reaction (PCR) inhibition was observed in DNA extracted from samples collected on the day of the dust storm. Testing over 45 days identified uneven geographic distribution suggesting Coccidioides hot spots. In 2016, highest daily concentration of arthroconidia was observed between September 25–October 20, and only sporadic low levels were detected after that. These results provide evidence of seasonality and uneven spatial distribution of Coccidioides in the air. Our results demonstrate that routine air monitoring for arthroconidia is possible and provides an important tool for Coccidioides surveillance, which can address important questions about environmental exposure and human infection.